Impact of COVID‐19 pandemic on ST‐elevation myocardial infarction in a non‐COVID‐19 epicenter - Hammad, Tarek A.; Parikh, Melanie; Tashtish, Nour; Lowry, Cynthia M.; Gorbey, Diane; Forouzandeh, Farshad; Filby, Steven J.; Wolf, William M.; Costa, Marco A.; Simon, Daniel I.; Shishehbor, Mehdi H. (Catheterization and cardiovascular interventions, 2021)
Objectives We sought to study the impact of COVID‐19 pandemic on the presentation delay, severity, patterns of care, and reasons for delay among patients with ST‐elevation myocardial infarction (STEMI) in a non‐hot‐spot region. Background COVID‐19 pandemic has significantly reduced the activations for STEMI in epicenters like Spain. Methods From January 1, 2020, to April 15, 2020, 143 STEMIs were identified across our integrated 18‐hospital system. Pre‐ and post‐COVID‐19 cohorts were based on March 23rd, 2020, whenstay‐at‐home orders were initiated in Ohio. We used presenting heart rate, blood pressure, troponin, new Q‐wave, and left ventricle ejection fraction (LVEF) to assess severity. Duration of intensive care unit stay, total length of stay, door‐to‐balloon (D2B) time, and radial versus femoral access were used to assess patterns of care. Results Post‐COVID‐19 presentation was associated with a lower admission LVEF (45 vs. 50%, p = .015), new Q‐wave, and higher initial troponin; however, these did not reach statistical significance. Among post‐COVID‐19 patients, those with >12‐hr delay in presentation 31(%) had a longer average D2B time (88 vs. 53 min, p = .033) and higher peak troponin (58 vs. 8.5 ng/ml, p = .03). Of these, 27% avoided the hospital due to fear of COVID‐19, 18% believed symptoms were COVID‐19 related, and 9% did not want to burden the hospital during the pandemic. Conclusions COVID‐19 has remarkably affected STEMI presentation and care. Patients' fear and confusion about symptoms are integral parts of this emerging public health crisis.